Cynical authorship and the Hong Kong studio system : Li Hanxiang and his Shaw Brothers erotic films - Teo, Stephen (2014)
This chapter presents the notion of Cynical authorship as a theoretical means to stake out possible new ground around the confluence of auteurism and collaboration. The chapter focuses on Li's authorship in relation to the Shaw Brothers Studio and the genre of the erotic films which became vastly popular in the 1970s, largely due to Li's creative efforts after he returned to the fold of Shaw Brothers following the failure of his own studio. These films became something of a specialty to Li. In tackling the question of authorship in this way, the chapter discusses authorship through a different cultural and national context (the Hong Kong Mandarin cinema) than that of most Western academic writing on the subject of the auteur or authorship so as to offer some reflections on the nature of film authorship.